Performance of broiler starter chicks fed higher concentrations of vitamin D3 at suboptimal levels of calcium and phosphorus in diet - RAO, S V RAMA; RAJU, M V L N; PANDA, A K; REDDY, M R; SUNDER, G SHYAM; SHARMA, R P (The Indian Journal of Animal Sciences, 2011)
An experiment was conducted with broiler starter chicks (1 to 21 d of age) to find out effect of higher concentrations of vitamin D3 CD3, 1200, 2400,4800 and 9600 lCUlkg) to basal diet (BD) containing lower concentrations of calcium (Ca, 0.4%) and non-phytate phosphorus (NPP, 0.2%). Areference diet (RD) containing 1.00/0 Ca, 0.450/0 NPP, 1200 lCU D::/kg was used for comparison. Each diet was fed to 11 battery brooder pens. Body weight gain, relative weight of tibia, tibia strength, tibia ash content, serum Ca concentration, activities of acid phosphotase (ACP) and alkaline phosphotase (ALP)in serum decreased significantly in broilers fed BD compared to those fed the RD. Supplementation of D3 to BD non-linearly increased body weight, bone weight and bone ash content, serum Ca concentration and activities of ACP and ALP. Supplementation of D3 to the BD linearly decreased excretion of all the minerals and Fe. In general, the retention of the trace minerals increased in pancreas and liver with increase in concentrations of D3 in the BD. The results indicated the possibility of increasing the performance and mineral utilization in broiler starters fed sub-optimal concentrations of Ca and NPP. However, a level of 9600 ICU Dikg in diets containing 0.4% Ca and 0.2% NPP appears to be inadequate to support body weight gain compared to those fed normal concentrations of Ca and NPP.Â